Implementation Of Nursing Care Documentation In The Inpatient Room - Irpan Ali Rahman; Heni Marliany; Lilis Lismayanti; Asep Gunawan (Jurnal Vocational Nursing Sciences (VNUS), 2019)
Objective, accurate and comprehensive documentation is the best factor to prove professional nursing actions and those given to patients as needed. Negligence or inaccuracies in making documentation will cause the nursing services provided to be unsustainable. Nurse workload is all activities or activities carried out by a nurse while on duty in a nursing service unit in the application of nursing care documentation. The method in this study uses a quantitative descriptive study with an observational approach to nursing care documents in the Inpatient Room at the Ciamis District Hospital. The population in this study were all 304 nurses who worked in the inpatient installation of the Ciamis District General Hospital. Sampling in this study used proportional random sampling so that the number of samples obtained was 75 nurses who worked in 13 inpatient installation rooms at the Ciamis District General Hospital. The results of the study showed that the implementation of nursing care documentation was mostly categorized as incomplete, as many as 41 people (54.7%).